Food beyond rights: where resistance meets cooperation - Valle, Gabriel, author (Colorado State University. Libraries, 2017)
One distinctive characteristic of life in the Anthropocene is uncertainty, but that uncertainty is not equally felt amongst the general population. In this essay, I argue that while the new norms of life in the Anthropocene may encourage a placeless, timeless world where individuals appear to be constantly at odds against their own existence, the so-called marginals make use of uncertainty to forge revolutionary subjectivities that enable new ways of being, seeing, and interacting with each other in the search of more just and sustainable worlds. The purpose of the essay is to describe the ways in which a group of low-income and recent immigrant gardeners, those who are often more exposed and vulnerable to the uncertainty of life in the Anthropocene, cultivate new subjectivities that forge alternative pathways toward justice in order to better their quality of life.
Presented at the Environmental justice in the Anthropocene symposium held on April 24-25, 2017 at the Lory Student Center, Colorado State University, Fort Collins Colorado. This symposium aims to bring together academics (faculty and graduate students), independent researchers, community and movement activists, and regulatory and policy practitioners from across disciplines, research areas, perspectives, and different countries. Our overarching goal is to build on several decades of EJ research and practice to address the seemingly intractable environmental and ecological problems of this unfolding era. How can we explore EJ amongst humans and between nature and humans, within and across generations, in an age when humans dominate the landscape? How can we better understand collective human dominance without obscuring continuing power differentials and inequities within and between human societies? What institutional and governance innovations can we adopt to address existing challenges and to promote just transitions and futures?
Keywords: urban agriculture; community garden; marginals; traditional environmental knowledge; TEK